Nonalcoholic Fatty Liver Hepatocyte-Derived lncRNA MALAT1 Aggravates Pancreatic Cell Inflammation via the Inhibition of Autophagy by Upregulating YAP. (31st August 2022) - Liu, Di; Yao, Weijie; Liu, Kejun; Wang, Genwang; Chen, Bendong; Wang, Zuozheng; Hou, Shaozhang
Abstract : Background . Acute pancreatitis (AP) is one of the most common gastrointestinal disorders, which causes death with a high mortality rate of about 30%. The study aims to identify whether the nonalcoholic fatty liver disease (NAFLD)-derived lncRNA MALAT1 participates in the inflammation of pancreatic cell and its potential mechanism. Methods . The NAFLD cell model was constructed by treating HepG2 cells with FFA. The in vitro model of acute pancreatitis (AP) was established by the administration of caerulein on AR42J cells. MALAT1 and si-MALAT1 were transfected into pancreatic cells, and then exosomes were collected from the NAFLD cell model and then were cocultured with AR42J cells. Transmission electron microscopy was used to observe the morphology of exosomes. Oil Red O staining was applied to reveal the lipid deposition. The triglyceride, IL-6, and TNF- α levels were detected using ELISA. The MALAT1 level in exosomes was detected by qRT-PCR. The CD9, CD63, CD81, and CYP2E1, LC3II, and LC3I levels were detected by western blot. Results . MALAT1 was upregulated in NAFLD-derived exosomes and increased the levels of IL-6 and TNF- α in pancreatic cells. NAFLD-derived exosomes inhibited YAP phosphorylation, decreased the levels of IL-6 and TNF- α, and reduced the ratio of LC3II/LC3I protein in pancreatic cells. Silencing MALAT1 significantly returned the inhibitory effect of NAFLD on hippo-YAP pathway. YAP1 signal transduction inhibitor CA3 reversed the decrease of LC3II/LC3I expression and the increase of IL-6 and TNF- α levels induced by MALAT1 in the AP cell model. Conclusions . NAFLD-derived MALAT1 exacerbates pancreatic cell inflammation via inhibiting autophagy by upregulating YAP.